Mitigating aflatoxin exposure to improve child growth in eastern Kenya - Hoffmann, Vivian; Jones, Kelly M.; Leroy, Jef L. (International Food Policy Research Institute, 2014)
An estimated 165 million children worldwide under age five have stunted growth (Black et al., 2013). Growth retardation in young children is associated with delays in cognitive development, lower school achievement, and lower earnings in adulthood. Data from the 2008-2009 De-mographic and Health Survey in Kenya suggest that 35 per-cent of children under age five in Kenya are stunted. What is intriguing is that the same data show that the former Eastern Province of Kenya has less poverty and lower prevalence of childhood illness than five of the other seven provinces in the country (KNBS and ICF Macro, 2010), yet stunting in this region is 20% higher than the national average. This suggests factors beyond poverty and illness are in affecting child growth here.